From the Helpdesk: Observations and guidance on educational response planning during the COVID-19 crisis (EdTech Hub, 2020)
Written by Rachel Chuang, Tom Kaye, Caitlin Moss Coflan & Arjun Upadhyay (EdTech Hub Helpdesk Management Team) Amid one of the biggest global disruptions to schooling in living memory, countries are quickly developing distance education responses for students. The EdTech Hub’s Helpdesk is providing evidence-informed responses to requests for support from governments and their partners as they face this challenge. …
KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707838 2405685:84ZQF884
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Library Catalog: edtechhub.org Section: general KerkoCite.ItemAlsoKnownAs: 2339240:35E4A2TD 2339240:4LGNB3A8 2339240:AA5FSXJC 2339240:RYJUP2SP 2405685:ATRDA7GD 2405685:BYEPNBQB 2405685:CLFVRHB5 2405685:EIZKB3Q4 2405685:QCXEVZTI 2405685:VMYU87NN 2405685:WWNJCJVG 2405685:ZFJGNIZJ 4656463:7UTAZK7R
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Learning through television in low-income contexts: mitigating the impact of coronavirus (COVID-19) - Watson, Joe (EdTech Hub, 2020)
This is part of our coronavirus (COVID-19) and EdTech series. Written by Joe Watson, research assistant at the University of Cambridge One of the many consequences of COVID-19 is that more than a billion caregivers will soon face the stark (and often scary) realisation that they must become their children’s teachers. This will be particularly difficult in low-income contexts where…
Library Catalog: edtechhub.org KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.4707800 2339240:ELSHST8I 2339240:NH74Q4D5 2339240:SEDLSMKA 2339240:SRTNHXEM 2339240:ZL8JVQGI 2405685:54S7693K 2405685:BGP7GCNU 2405685:DLE5F2DK 2405685:FF93KYQR 2405685:LA5D6QFR 2405685:PCDTZ7S3 2405685:PD7SX3IX 2405685:SS7E2HN4 2405685:VCLDWRIS 4803016:U4W8F4AZ BGP7GCNU SEDLSMKA
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH